The knowledge that matters in professional practices - Edwards, A; Daniels, H (2012)
We draw on the analytic resources of cultural historical activity theory and the work of (Basil) Bernstein and Knorr Cetina to examine evidence from a study of inter-professional practices in children's services in three English local authorities (local government systems). The study traced the horizontal (e.g. cross service) and vertical (e.g. between strategy and operation) integration of services for children including social work and educational psychology at time of reductions in local authority funding. Interviews and meetings, structured by the principles of developmental work research, required senior local authority staff to identify the objects of activity that shaped the work of the services for which they were responsible, to reveal how those objects were threatened by changing configurations of services and to reflect on what features of the services should be taken forward in these reconfigurations. The study therefore made visible the motives that become evident when professional knowledge is brought to bear on problems of professional practices. In examining the interplay between professional knowledge - which includes notions of the service ideal - and objects of activity, we identified 'what matters' in practices within services and 'what matters' when practices intersect and objects of activity are negotiated across practice boundaries. © 2012 Copyright Taylor and Francis Group, LLC.